Loosening the Shackles of the Truth Defence on Freedom of Speech: Making Defamation Law's Truth Defence More User Friendly for Media Defendants - Fernandez, Joseph (N/A, 2010)
The truth defence is defamation law's oldest defence but it remains the least attractive defence to Australian media defendants because of its onerous threshold for success. The paper argues that the shackles on the truth defence are inconsistent with established freedom of speech ideals and the public interest in having a robust media. As a result society is constrained from enlightened participation in public affairs. This paper proposes reforms to alleviate the heavy demands of the defence so as to promote the discussion of matters of public concern and to strike a more contemporary balance between freedom of speech and the protection of reputation. These reforms employ defamation law's doctrinal calculus to reposition the protection of reputation/freedom of speech fulcrum. The cornerstone of the reform proposals considered here is one that advocates a reversal of burdens so that the plaintiff bears the burden of proving falsity of the defamatory publication where the complainant is a public figure; the matter complained about is a matter of public concern; and the legal action is against a media defendant.